Analysis of Factors Influencing the Recycling Behavior of Electric Vehicle Batteries in East Kalimantan - Bening Zirah Hasbi; Muriani Emelda Isharyani; Dutho Suh Utomo (Poltanesa, 2026)
The increasing use of electric vehicles poses challenges in managing batteries that have reached the end of their lifespan, making user behavior in recycling an important factor in supporting the sustainability of the electric vehicle system. This study aims to analyze the factors influencing the recycling behavior of electric vehicle batteries among electric vehicle users in East Kalimantan by using part of the Comprehensive Action Determination Model (CADM). The study employs multiple linear regression to examine the effects of Perceived Behavioral Control (PBC), Recycling Intention (RI), and Recycling Habit (RH) on Recycling Behavior (RB). Data were collected from the perceptions of 82 electric vehicle users in East Kalimantan through a questionnaire. The results show that RH significantly affects RB, while PBC and RI do not have a partial effect. However, all three variables simultaneously influence the recycling behavior of electric vehicle batteries. These findings indicate that habit formation plays a crucial role in encouraging recycling behavior. Therefore, improving recycling behavior should begin with forming recycling habits in the community, which can then be strengthened through increased knowledge and intention. The government can support this by promoting awareness of electric vehicle battery waste management and gradually strengthening recycling programs to habituate the public to recycling activities